Gambaran Kesiapan Kognitif dalam Pengajaran Bahasa Inggris pada Program Studi Pendidikan Bahasa Inggris di Universitas Swasta - lulu Atul Munawaroh; Imam Santosa (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2026)
This study explores freshmen’s cognitive readiness in English Language Teaching (ELT) at a private university and identifies the factors that shape their readiness in the early stage of higher education. Cognitive readiness is important in ELT because it supports students’ ability to participate in classroom interaction, solve learning problems, make academic decisions, regulate emotions, and adapt to new learning demands. This study employed a qualitative case study design involving thirteen freshmen from the English Language Education Department. The participants were selected through purposive sampling from three campus branches. Data were collected through semi-structured interviews and a closed-ended questionnaire, then analyzed using thematic analysis supported by descriptive statistics. The findings show that freshmen demonstrated strong readiness in teamwork and communication, reflected in their ability to collaborate, ask questions, share ideas, and receive feedback during learning activities. Emerging readiness was found in decision-making, problem-solving, adaptability, leadership, and mental flexibility and creativity. Limited readiness appeared in metacognition, automaticity, memory, emotion, and transfer of learning, indicating that several students still needed support in independent learning, self-reflection, emotional control, and applying prior knowledge to new contexts. Five factors were identified as shaping cognitive readiness: cultural-related experiences, parental involvement, self-efficacy, psychological-mindedness, and maladaptive beliefs, with cultural-related experiences emerging as the most dominant factor. The study suggests that ELT lecturers need to design learning activities that balance collaboration, reflection, emotional support, and independent learning practice.